Thyroid hormones and depression: The health in men study - Almeida, O.; Alfonso, Helman; Flicker, L.; Hankey, G.; Chubb, S.; Yeap, B. (2011)
Context: Current practice guidelines suggest that thyroid function tests should be an integral part of the assessment of adults presenting with a depressive episode, although there is a paucity of data available to support such a recommendation. Objective: To determine if biochemical markers of thyroid dysfunction are associated with prevalent and incident clinically significant depressive symptoms. Design: Cross-sectional and cohort studies. Patients: Community-dwelling sample of 3,932 men age 69 to 87 free of overt thyroid disease. Main Outcome Measures: We used the 15-item Geriatric Depression Scale to ascertain the presence of prevalent clinically significant depressive symptoms, and the Western Australia Data Linkage System to establish the onset of a depressive episode according to the International Classification of Diseases. Results: The serum concentration of thyroid-stimulating hormone and free thyroxine (fT4) did not affect the odds of prevalent or the hazard of incident depression. The odds of prevalent depression were 0.8 (95% CI: = 0.5-1.3) for men with subclinical hypothyroidism and 1.4 (95% CI: = 0.3-5.8) for those with subclinical hyperthyroidism. The hazard ratio of incident depression associated with subclinical hypothyroidism was 0.7 (95% CI: = 0.3-1.9). No men with subclinical hyperthyroidism developed depression during the follow-up period of 5.5 ± 1.4 years. Conclusions: Subclinical thyroid disease is not associated with prevalent or incident depression in older men. These findings do not support the routine screening of subclinical thyroid dysfunction among older adults with depression. © 2011 American Association for Geriatric Psychiatry.